Fusarium casha sp. nov. and F. curculicola sp. nov. in the Fusarium fujikuroi Species Complex Isolated from Amaranthuscruentus and Three Weevil Species in South Africa - Marcele Vermeulen; Lisa A. Rothmann; Wijnand J. Swart; Marieka Gryzenhout (Diversity, 2021)
Trials are currently being conducted in South Africa to establish Amaranthus cruentus as a new pseudocereal crop. During recent surveys, Fusarium species were associated with weevil damage in A. cruentus fields. Preliminary studies showed that some of these Fusarium species grouped into two distinct clades within the F. fujikuroi species complex. The aim of this study was to characterize these isolates based on the morphology and phylogeny of the translation elongation factor 1α (TEF1α) gene region, ß-tubulin 2 (ßT) gene region and RNA polymerase II subunit (RPB2), and to determine if these isolates are pathogenic to A. cruentus. Phylogenetic and morphological studies showed that these two clades represent two novel species described here as F. casha and F. curculicola. Both species were shown to have the potential to be pathogenic to A. cruentus during routine greenhouse inoculation tests. While isolations indicate a possible association between these two species and weevils, further research is needed to understand this association and the role of weevils in disease development involving F. casha and F. curculicola in A. cruentus.